The Impact of Artificial Intelligence (AI) News Virality on Public Perception in Indonesia in 2025 - Putri Indriani; Sadam Rahmat Putra; Akbar Kurnia; Suci Permata Nadia Pasaribu (Penerbit Hellow Pustaka, 2026)
This study aims to determine the influence of news virality regarding Artificial Intelligence (AI) on public perception in Indonesia in 2025. The rapid development of AI, accompanied by the massive dissemination of information through social media and digital platforms, has created a wave of diverse public opinion, ranging from enthusiasm for innovation to concern about the socio-economic impacts. This study used a quantitative approach with a survey method of 150 respondents aged 17–50 who are active on social media. Data were collected through an online questionnaire and analyzed using descriptive statistics, Pearson correlation, and simple linear regression. The results show a positive and significant relationship between AI news virality and public perception, with a correlation value of 0.487 and a significance level of p < 0.05. The greater the intensity of exposure to AI viral news, the stronger its influence on shaping public perception. These findings demonstrate the important role of the media in presenting balanced information and the need to improve digital literacy amidst the rapid and often inaccurate flow of technological information.